Progressive dehydration in junior Laser class sailors during World Championship - Arnaoutis, G.; Verginadis, P.; Seal, A. D.; Vogiatzis, I.; Sidossis, L. S.; Kavouras, S. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
The purpose of this article is to assess the hydration status of elite young sailing athletes during World Championship competition. Twelve young, elite, male, Laser Class sailors (age: 15.8 ± 1.1 y, height: 1.74 ± 0.1 m, weight: 65.1 ± 1.5 kg, body fat: 12.5 ± 3.1%, training experience: 7.0 ± 1.2 y) participated in this descriptive study. After three-day baseline bodyweight measurements, hydration status was assessed via pre- and post-race body weights, urine-specific gravity, and thirst ratings via a visual analog scale during four consecutive days of racing. Measurements and data collection took place at the same time each racing day, with mean environmental temperature, humidity, and wind speed at 23.0 ± 0.8°C, 64-70%, and 9 ± 1 knots, respectively. Average racing time was 130 ± 9 min. Body weight was significantly decreased following each race-day as compared to prerace values (Day 1: -1.1 ± 0.2, Day 2: -2.5 ± 0.1, Day 3: -2.8 ± 0.1, and Day 4: -3.0 ± 0.1% of body weight; p < 0.05). The participants exhibited dehydration of -2.9 ± 0.2 and -5.8 ± 0.2% of body weight before and after the fourth racing day as compared to the three-day baseline body weight. Urine-specific gravity (pre-post Day 1: 1.014-1.017; Day 2: 1.019-1.024; Day 3: 1.021-1.026; Day 4: 1.022-1.027) and thirst (pre-post ? Day 1: 2.0-5.2; Day 2: 3.2-5.5; Day 3: 3.7-5.7; Day 4: 3.8-6.8) were also progressively and significantly elevated throughout the four days of competition. The data revealed progressive dehydration throughout four consecutive days of racing as indicated by decreased body weight, elevated urine concentration, and high thirst.